Acute heart failure as an atypical presentation of Takayasu arteritis: The value of multi‐modality imaging. Issue 1 (25th January 2022) - Djafari Naeini, Sepideh; Bayat, Fariba; Houshmand, Golnaz
Abstract: Takayasu arteritis (TA) is an inflammatory disease that affects the aorta and the major branch arteries. Here, we describe an atypical presentation of the disease with heart failure. Abstract : Multi‐modality imaging, particularly the use of cardiac magnetic resonance, is considerably helpful in diagnosing and managing Takayasu arteritis (TA). In the workup of new‐onset heart failure in young patients employing cardiac MRI can be promising in making the proper diagnosis and subsequent treatment.